INTEGRASI TARI TOR-TOR DALAM KURIKULUM MERDEKA: ANALISIS POTENSI BUDAYA UNTUK PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Hutagalung, Doni; Handoyo, Eko; Aricindy, Argitha; Indriana Eko Amaidi (Universitas Negeri Medan, 2025)
This study aims to analyze the integration of the Tor-Tor dance into the Merdeka Curriculum as a means of developing character in elementary school students. Tor-Tor dance, as a Batak cultural heritage rich in ethical, social, and spiritual values, has the potential to instill discipline, cooperation, and responsibility among learners. The research employs a qualitative literature review approach, examining curriculum documents, character education theories, and cultural sources related to Tor-Tor dance. The analysis reveals that Tor-Tor dance can serve as an effective learning medium by combining cognitive, affective, and psychomotor aspects while reinforcing local cultural identity. The study emphasizes the importance of incorporating culturally based teaching materials to support character development grounded in the noble values of the nation.